Compétition entre villes pour l’Olympe - Charles-Edouard Houllier-Guibert (Netcom)
Three French cities are promoting their mobilization in official websites, for the bid of the Olympic Winter Games 2018. Presentation of the city, construction of arguments that make up these sites are tools to vague objectives. Each city is trying to show the differentiating elements that ultimately rather banal whereas each website is organized to convince the selectors to select the best area. In a marketing lecture, the difficulty of urban differentiation can be explained by taking into account systematically the local population, who is the true target of the websites.